Fiqh Humanism in Interfaith Relations: Sufistic Expressions of Shalawat Wahidiya in Indonesia - Bustanul Arifin; Diyan Putri Ayu; Ahmad Insya Ansori; Muhammad Misbahuddin; Safa Alrumayh (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study examines how fiqh humanism can be operationalised as a lived legal–ethical framework through the Sufistic practices of Shalawat Wahidiya in Indonesia. The research addresses the question of how Islamic legal objectives (maqāsid al-sharīa) are translated into concrete interfaith engagement and social ethics in a plural religious context. Positioning itself within maqāsid-oriented jurisprudence and contemporary Sufism studies, the article argues that Islamic law does not need to be limited to normative abstraction or legal formalism, but it can function as an ethical system verified through social practice. Methodologically, the study employs a convergent mixed-methods design, integrating a survey of 382 respondents with participant observation, in-depth interviews in Jombang, East Java and document analysis. Quantitative data map patterns of inclusivity, interfaith attitudes, and community sustainability, while qualitative findings explain how these patterns are ethically internalised and institutionally organised. The findings demonstrate that Wahidiya operates as a living maqāsid system, where collective dhikr, ritual openness, and consultative governance foster emotional security, interfaith comfort, and social cohesion without weakening Islamic commitment. The study contributes theoretically by advancing fiqh humanism as an empirically verifiable framework and provides a model that can be used to analyse Islamic legal and spiritual practices in diverse societies.